2018
DOI: 10.1007/s00431-018-3153-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thrombocytopenia—causes and outcomes following platelet transfusions

Abstract: We evaluated the causes for neonatal thrombocytopenia (NT), the duration of NT, and the indications of platelet transfusions (PT) by means of a retrospective cohort study over a 23-year period. Neonates with NT were identified via ICD-10 code D69.6. Of 371 neonates (1.8/1000 live births) with NT, the majority (312; 84.1%) had early onset thrombocytopenia, and 282 (76%) were preterm born. The most frequent causes for NT were early and late onset sepsis and asphyxia. The mean duration of thrombocytopenia was 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 46 publications
6
67
7
Order By: Relevance
“…In our study, there were no statistically significant differences between duration of hospital stay and severity of NT, which did not agree with Resch et al [23], as they found the duration of NT is positively related to the severity of NT and the number of subsequent platelet transfusions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, there were no statistically significant differences between duration of hospital stay and severity of NT, which did not agree with Resch et al [23], as they found the duration of NT is positively related to the severity of NT and the number of subsequent platelet transfusions.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore in our study, most cases of NT in term infants were late onset (after 72hours of life) in about two-thirds of the cases. This was not in agreement with another study in which the majority (84.1%) had early onset NT, but 76% of cases were born preterm [9].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…To ensure robustness of ECE, we checked the association of the final set of ECE with clinically relevant outcomes in the published literature. [23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Phase Ii: Pilot Testing Of Ewc To Determine Ecesmentioning
confidence: 99%